Mujer que liba, de Pilar Sanabria Cañete (Castilla. Estudios de Literatura, 2026)
Review of the poetry collection Mujer que liba by Pilar Sanabria
Keywords: Review; Pilar Sanabria; Poetry; Mujer que liba